Den gröna slaktaren - Jönsson, Håkan (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
Even in the older of industries: food production, there is a lot of talk about a new time, rapid changes and selling experiences instead of products. As an example of the new type of "value added products", the article examines the concept "The Green Butcher": a range of cured meats with a low content of fat. The author argues that the green colour partly explains the Green Butcher’s success. By being green, it combines the two main experiences that are commercialised in the food business: the rational and controlled body and the hedonist person. This seems to be a contradiction, and so it is. But it is the same contradiction as our bodies must try to contain in a time in which it is the thin, controlled body that is supposed to have all the great hedonistic experiences. The green butcher (but not its colourless competitors) therefore provides an opportunity to consume a solution to an always present problem.